2016
DOI: 10.1039/c6ob01980c
|View full text |Cite
|
Sign up to set email alerts
|

Convenient protocols for Mizoroki–Heck reactions of aromatic bromides and polybromides with fluorous alkenes of the formula H2CCH(CF2)n−1CF3 (n = 8, 10)

Abstract: The fluorous alkenes HC[double bond, length as m-dash]CHR (R = (CF)CF; n = 8, 10) undergo the Mizoroki-Heck reaction with a variety of aromatic monobromides and polybromides such as 1,3- and 1,4-CHBr, 1,3,5-CHBr, 1,3,5-CHBrCl, 1,4-XCHBr (X = CF, R, COCH, CN, 1,4-OCHBr), 1,2-ONCHBr, 5-bromoisoquinoline, 5-bromopyrimidine, 3-bromo-5-methoxypyridine, and 3,5-dibromopyridine (sixteen examples, 78% average isolated yield). Typically, 1.2-2.4 equiv. of alkene are employed per Ar-Br bond, together with Pd(OAc) cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As shown in Scheme 1 , related fluorous aryliodine(III) dichlorides with three-methylene spacers, (R f8 CH 2 CH 2 CH 2 ) 2 C 6 H 3 ICl 2 , had been isolated (the isomers III , IV ) [ 17 ]. Recently, a potential precursor with two-methylene spacers, 1,3-(R f8 CH 2 CH 2 ) 2 C 6 H 4 , became readily available [ 49 ]. Accordingly, it could be iodinated with I 2 /H 5 IO 6 as shown in Scheme 6 (bottom) to give 1,2,4-(R f8 CH 2 CH 2 ) 2 C 6 H 3 I [ 50 ] in 93% yield after work-up.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 1 , related fluorous aryliodine(III) dichlorides with three-methylene spacers, (R f8 CH 2 CH 2 CH 2 ) 2 C 6 H 3 ICl 2 , had been isolated (the isomers III , IV ) [ 17 ]. Recently, a potential precursor with two-methylene spacers, 1,3-(R f8 CH 2 CH 2 ) 2 C 6 H 4 , became readily available [ 49 ]. Accordingly, it could be iodinated with I 2 /H 5 IO 6 as shown in Scheme 6 (bottom) to give 1,2,4-(R f8 CH 2 CH 2 ) 2 C 6 H 3 I [ 50 ] in 93% yield after work-up.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the atom connectivity could be assessed to confirm the successful functionalization and a coplanar orientation of the FAA group with aromatic rings. As a further comparison, we synthesized compound 5 in 86% isolated yield using the microwave and obtained a higher yield than 76%, reported by Su et al 17 Conditions B were also shown to be compatible with the installation of C 6 F 13 chains (compound 6, 42% yield) and to tolerate pyridine groups (compound 7, 31% yield), although the yields with the shorter fluorocarbons were slightly lower than the C 8 F 17 chain analogues. All products are soluble in common organic solvents and could be easily isolated in pure form by silica gel column chromatography.…”
mentioning
confidence: 82%
“…Fluoroalkyl alkenes (FAAs) are affordable and accessible precursors, providing an impressive potential of fluorinated material discovery (Figure 1, c). FAAs were first utilized in Pd-catalyzed Heck reactions by Chen and co-workers 14,15 and have been demonstrated to react with aryl halides, [14][15][16][17][18] aryl diazonium salts, 19,20 and aryl boronic acids. 21 However, the substrate scope in these reports was mostly limited to phenyl groups, with a few exceptions including nitrogen-containing heterocycles, 18 naphthyl groups, 20 binaphthyl groups, 14,15,22 and perylene bisimides.…”
mentioning
confidence: 99%
“…Moreover, 77 could be easily separated by F-SPE (Fluorous solid phase extraction) technique and reused three times without significant loss of activity. Gladysz and co-workers reported a convenient and scalable procedure for the cross-couplings of fluorous alkenes (80) with aryl bromides (81) using a modified Jeffery version of the Mizoroki-Heck reaction (Scheme 16) [72]. Fluorous alkenes (80) reacted with aryl monobromides and polybromides (81), such as 1,3-and 1,4-C 6 H 4 Br 2 , 1,3,5-C 6 H 3 Br 3 , 1,3,5-C 6 H 3 Br 2 Cl, 1,4-XC 6 H 4 Br (X = CF 3 , C 8 F 17 , COCH 3 , CN, 1,4-OC 6 H 4 Br), 1,2-O 2 NC 6 H 4 Br, 5-bromo-isoquinoline, 5-bromopyrimidine, 3-bromo-5-methoxypyridine, and 3,5-dibromopyridine, under the modified Mizoroki-Heck coupling conditions to afford the corresponding fluorophilic adducts (82) in good to high yields.…”
Section: Fluoroalkylated Alkenes As the Cross-coupling Partnersmentioning
confidence: 99%